Sustainability in Peri-Urban Informal Settlements: A Review - Carrilho, João (2022)
The study of peri-urbanization attracted attention in the final quarter of the 20th century, due to the pace it acquired worldwide and the implication that urbanization and overall settlement patterns have on social sustainability and development. Theoretical and conceptual achievements are remarkable. Multi-country collaboration has produced a growing body of research on sustainability and peri-urban settlements. There is a lack, however, of a review of the practices of peri-urban informal settlements, the predominant mode of urban expansion, mainly in developing and rapidly urbanizing regions of the world. The purpose is, then, to systematize, from recent literature, the knowledge of the context, challenges, and practices, as well as their impacts and potential courses of action, to ensure sustainability in human–natural complex of the territory beyond urban cores, suburbs, or slums. A systematic review approach was adopted, for articles published in reputable journals, with support of previous reviews, books, and reports. A pragmatist combination of content analysis and critical review identified core topics and highlighted contrasting views. An analytical framework is proposed. Four categories—drivers, challenges and practices, impact, and future trends—are proposed as an adequate approach to systematizing the literature. The review finds that the practices focus on service and resource provision, on regulations to approximate informal to formal institutions, and on an economy founded on the resource base and service provision. This review provides insights on future trends and research topics